Exenatide and sitagliptin decrease interleukin 1β, matrix metalloproteinase 9, and nitric oxide synthase 2 gene expression but does not reduce alveolar bone loss in rats with periodontitis - Moraes, Renata M. [UNESP]; Lima, Gabriela M G [UNESP]; Oliveira, Felipe E. [UNESP]; Brito, Ana Carolina V [UNESP]; Pereira, Rodrigo C. [UNESP]; Oliveira, Luciane D. [UNESP]; Barros, Patrícia P. [UNESP]; Franco, Gilson C N; Anbinder, Ana Lia [UNESP] (Journal of Periodontology, 2015)
New drugs for the treatment of diabetes, glucagon-like peptide-1 (GLP-1) receptor agonists and inhibitors of dipeptidyl peptidase-4 (DPP-4) have shown pleiotropic effects on bone metabolism and anti-inflammatory properties. The aim of this study is to evaluate the effects of exenatide (GLP-1 agonist) and sitagliptin (DPP-4 inhibitor) during periodontitis induction by ligature insertion in rats. Forty rats were divided into four groups: 1) animals with induced periodontitis that received exenatide (EG); 2) animals with induced periodontitis that received sitagliptin (SG); 3) animals with induced periodontitis and without drug treatment (LG); and 4) animals without induced periodontitis and without drug treatment (controls). The drugs were administered for 28 days. On the day the animals were sacrificed, blood was collected for analysis of glucose and DPP-4 levels. The gene expressions of prostaglandin-endoperoxide synthase 2, tissue inhibitor of metalloproteinase 1, Dpp4, nitric oxide synthase 2 (Nos2), interleukin 1β (Il1b), and matrix metalloproteinase 9 (Mmp9) in the gingiva; support and alveolar bone loss; connective tissue attachment; and the quantity of gingival collagen were evaluated. Exenatide and sitagliptin treatments have led to a lower percentage of weight gain but did not influence glycemia. Sitagliptin reduced the serum concentration of DPP-4. Interestingly, although the gene expression profile has revealed a downregulation of Mmp9, Nos2, and Il1b in both EG and SG compared to LG, a significant protective effect was not observed on alveolar bone and collagen tissue in this model. Regardless of the reduction of the expression of Il1b, Nos2, and Mmp9, the drugs were not effective in the stabilization or reduction of alveolar bone loss and collagen degradation in rats.
Keywords: Alveolar bone loss; Diabetes mellitus; Dipeptidyl peptidase 4; Incretins; Periodontitis alveolar bone loss